2017
DOI: 10.1080/10408398.2017.1296408
|View full text |Cite
|
Sign up to set email alerts
|

Extremozymes from metagenome: Potential applications in food processing

Abstract: The long-established use of enzymes for food processing and product formulation has resulted in an increased enzyme market compounding to 7.0% annual growth rate. Advancements in molecular biology and recognition that enzymes with specific properties have application for industrial production of infant, baby and functional foods boosted research toward sourcing the genes of microorganisms for enzymes with distinctive properties. In this regard, functional metagenomics for extremozymes has gained attention on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 104 publications
0
10
0
Order By: Relevance
“…Thus, extremozymes are ideal tools for industrial applications where harsh chemical and physical conditions are encountered. However, the difficulties in cultivating extremophiles severely limit access to this class of biocatalysts, thereby metagenomic approaches are now largely used for extremozyme discovery [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, extremozymes are ideal tools for industrial applications where harsh chemical and physical conditions are encountered. However, the difficulties in cultivating extremophiles severely limit access to this class of biocatalysts, thereby metagenomic approaches are now largely used for extremozyme discovery [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The interest in extremophiles has boosted metagenomics studies of extreme environments [12][13][14][15][16], and, more recently, remarkable examples of the discovery of novel extremozymes for industrial applications from sequence-based screenings have been reported [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Further developments in sequencing, computation and bioinformatics might solve the problems associated with data mining for extremozymes and can help overcome the annotation difficulties in the near future. So far, we are currently seeing a boom of culture-independent methods for bioprospection of novel extremozymes from environmental metagenomes, which will help feed in the databases, opening the possibility to isolate and functionally characterize genes from unculturable extremophilic microorganisms (Khan and Sathya, 2018;Verma and Satyanarayana, 2020;Sysoev et al, 2021). On the other hand, there is a culture dependent functional approach for the discovery and development of novel extremozymes, which has been largely used over the years with proven successful results (Caceres-Moreno et al, 2019;Espina et al, 2020).…”
Section: Discovery Development and Production Of Novel Extremophilic Oxidoreductasesmentioning
confidence: 99%